Udbredelsen af reguleret møntøkonomi i geografisk perspektiv ca. 600 - ca. 1150 - Moesgaard, Jens Christian (Hikuin, 2008)
The introduction of a regulated coin economy in a geographical perspective, c. 600-ca. 1150 By Jens Christian Moesgaard In Viking-Age Denmark, coins were predominantly used by weight along with ingots and other silver artefacts. They were bent and pecked in order to test the alloy, and they were cut to make up small change. However, another form of coin use emerged at various places and at various times: the use at tale (by number) in a regulated currency, the way we use coins today. This system required a powerful coin issuer to guarantee the coin value, and coin users ready to accept it. The study of coin issues and circulation reveals that coins were used at tale in Ribe during the 8th-9th centuries, perhaps in Haithabu in the 9th century, and for certain in south-eastern Schleswig in the 10th century. A tentative attempt was made in the 970s and 980s to introduce a regulated currency on a national scale. During the 11th century, a regulated currency slowly evolved, first in the cities and by the third quarter of the century all over the country except in Bornholm and Blekinge, where the weight economy was maintained well into the 12th century.